2013
DOI: 10.1098/rspb.2013.0305
|View full text |Cite
|
Sign up to set email alerts
|

Living on the edge: how philopatry maintains adaptive potential

Abstract: Without genetic variation, species cannot cope with changing environments, and evolution does not proceed. In endangered species, adaptive potential may be eroded by decreased population sizes and processes that further reduce gene flow such as philopatry and local adaptations. Here, we focused on the philopatric and endangered loggerhead sea turtle (Caretta caretta) nesting in Cape Verde as a model system to investigate the link between adaptive potential and philopatry. We produced a dataset of three complem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
88
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 71 publications
(96 citation statements)
references
References 63 publications
4
88
1
Order By: Relevance
“…Occurrence of philopatry in association with a nonrandom pattern of geographic variation in small genomic regions was reported recently (Stiebens et al . ) in a study of variation in MHC alleles among philopatric loggerhead turtles in the Cape Verde Archipelago. Both mtDNA haplotypes and MHC alleles were structured genetically among nesting islands, but only nuclear‐encoded microsatellites followed a geographic pattern, in this case one of isolation by distance indicative of restricted male dispersal.…”
Section: Discussionmentioning
confidence: 99%
“…Occurrence of philopatry in association with a nonrandom pattern of geographic variation in small genomic regions was reported recently (Stiebens et al . ) in a study of variation in MHC alleles among philopatric loggerhead turtles in the Cape Verde Archipelago. Both mtDNA haplotypes and MHC alleles were structured genetically among nesting islands, but only nuclear‐encoded microsatellites followed a geographic pattern, in this case one of isolation by distance indicative of restricted male dispersal.…”
Section: Discussionmentioning
confidence: 99%
“…[18,22,23] with (ii) recently trailed at sea acoustic tracking [31] and (iii) high-resolution ocean model data [32]. We focused on the Cape Verde Islands which host the World's third largest [33], and highly philopatric [34] nesting population of loggerhead turtles which are genetically isolated from other Atlantic and Mediterranean rookeries [12]. Owing to the oceanic location of these islands, this nesting aggregation is exposed to very different ocean current regimes than coastal mainland sites where studies into loggerhead turtle hatchling swimming behaviour have focused.…”
Section: Introductionmentioning
confidence: 99%
“…After amplification and cleaning of PCR product using EXoSap, sequences were loaded into an ABI 3730 Genetic Analyzer (Applied Biosystems, Darmstadt, Germany). For more details, see Stiebens et al [32]. Four different haplotypes were found: CcA1.3, CcA17.1, CcA17.2 and CcA2.1 following the Archie Carr Center for Sea Turtle Research nomenclature (http://accstr.ufl.edu/resources/mtdna-sequences/).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, Monzon-Arguello et al [31] revealed the significant genetic divergence between the Cape Verde rookery and other Atlantic and Mediterranean rookeries. Furthermore, Stiebens et al [32] showed strong signs of philopatry at the island level, suggesting a complex structure of the rookery with independent colonies. Additionally, in Cape Verde, the fungus Fusarium solani was found to be the cause of infections in turtle eggs that accounted for over 80% of mortality in a challenged experiment [33], supporting the need to characterize immune relevant genes.…”
Section: Introductionmentioning
confidence: 99%